Changes in whole-blood PUFA and their predictors during recovery from severe acute malnutrition. Issue 10 (21st March 2016) - Babirekere-Iriso, Esther; Mortensen, Charlotte G.; Mupere, Ezekiel; Rytter, Maren J. H.; Namusoke, Hanifa; Michaelsen, Kim F.; Briend, André; Stark, Ken D.; Friis, Henrik; Lauritzen, Lotte
Abstract: Children with severe acute malnutrition (SAM) with complications require in-patient management including therapeutic feeding. Little attention has been given to the effects of these feeds on the essential fatty acid status of children with SAM. The objective of this study was to describe changes in the PUFA composition in whole blood in children with SAM during treatment and to determine predictors of change. This prospective study took place in a paediatric nutrition rehabilitation unit in Kampala, Uganda, and assessed whole-blood fatty acid composition of children with SAM at admission, transition, discharge and follow-up (8 and 16 weeks). ANCOVA was used to identify predictors of change in whole-blood PUFA. The study included 120 children with SAM and twenty-nine healthy control children of similar age and sex. Among the SAM children, 38 % were female and 64 % had oedema. Whole-blood n -6 PUFA proportions increased from admission to follow-up, except for arachidonic acid, which decreased by 0·79 (95 % CI 0·46, 1·12) fatty acid percentage (FA%) from admission to transition and 0·10 (95 % CI 0·23, 0·44) FA% at discharge. n -3 Long-chain (LC) PUFA decreased by 0·21 (95 % CI 0·03, 0·40) FA% at discharge and 0·22 (95 % CI 0·01, 0·42) FA% at 8 weeks of follow-up. This decrease was greater in children from families with recent fish intake and those with nasogastric tube feeding. Current therapeutic feeds do not correct whole-blood levels of LCPUFA, particularly n -3 LCPUFA, in children with SAM. Increased attention is needed to the contents of n -3 LCPUFA in therapeutic feeds.